An examination into the role of a peer academic online mentoring programme during Emergency Remote Teaching at a South African residential university - Ontong, J. M.; Arendse-Fourie, S.; Schonken, C. (South African Journal of Higher Education, 2021)
For residential universities, the COVID-19 pandemic in the 2020 academic year necessitated the suspension of in-person lectures and a swift transition of classes and other in-person activities to emergency remote teaching (ERT). This included the academic module mentoring programme, cognisant of the potential challenges experienced by first-year students during a period of ERT. The role of an in-person module mentoring programme before ERT was only to provide academic support to first-year students within an introductory financial accounting module to promote student success. This study investigated the role of an academic online mentoring programme for students in an introductory financial accounting module during ERT. A web-based survey was conducted to source the perceptions of both mentors and mentees who participated in an introductory module academic mentoring programme both before and during ERT to analyse whether the role of the academic module mentoring programme had shifted beyond that of academic support in an ERT environment. While academic support remained at the forefront as the main perceived benefit of the online mentoring programme, with the transition to ERT, the findings of this study illustrate an altering role that is more inclusive of additional psychological and peer support and engagement perceived benefits for first-year students who participated in an academic mentoring programme for students in an introductory financial accounting module during a period of ERT. Understanding student perceptions of the value derived for first-year students from an academic online mentoring programme is important in understanding first-year student needs and to provide relevant and applicable training to first-year students to promote student success during ERT. The findings of this study provide insight to institutions and in considering the addition of academic interventions such as offering academic online mentoring programmes during ERT and highlight the perceived value-add from both a mentor and mentee perspective.